The Short-Run and Long-Run Effects of Central Bank Rate on Exchange Rate Volatility in Indonesia - Suhendra, Indra; Anwar, Cep Jandi; Istikomah, Navik; Purwanda, Eka; Kholishoh, Lilis Nur (International Journal of Innovative Research and Scientific Studies, 2022)
This research measures the short and long-run effects of central bank policy rate on the volatility of the exchange rate in Indonesia using the quarterly data from Q1 1992 to Q4 2019. The process involves applying an Autoregressive Distribution Lag estimation to investigate the effects of the variables. The exchange rate volatilities include Indonesia Rupiah to US Dollar (IDR-USD), Indonesia Rupiah to Singapore Dollar (IDR-SGD), Indonesia Rupiah to Australia Dollar (IDR-AUD), Indonesia Rupiah to British Pound Sterling (IDR-GBP), and Indonesia Rupiah to Euro (IDR-EURO). Several results were obtained and the first to show the adjustment time for exchange rate volatility to achieve long-run equilibrium was 1.77 quarters to 2.26 quarters using the ARDL estimation. Secondly, a decrease in the central bank rate was found to significantly reduce the exchange rate volatility in the short run and long run. These results are robust since Full Modified Ordinary Least Square (FMOLS) estimation was applied for all five models. Furthermore, it was found that in the long run, the central bank policy rate had a significant positive effect on the volatility of the Indonesia Rupiah against five foreign exchange rates. Therefore, it was suggested that the policymakers need to keep the interest rate of the central bank low and stable to ensure the Rupiah exchange rate stability.